Diffraction pattern by rotated conical tracks in solid state nuclear track detectors. (June 2016) - Stevanovic, N.; Markovic, V.M.
Abstract: The method for determination of diffraction pattern for irregular 3D objects with application on rotated conical tracks in solid state nuclear track detector (SSNTD) wasdescribed in this paper. The model can be applied for different types of the diffraction (Fresnel, Fraunhofer) and arbitrary shapes of the obstacle. By applying the developed model on conical tracks it was fond that diffraction pattern strongly depends from radius, length and rotation angle of the conical tracks. These dependences were investigated in this paper and results can be applied for determination of inner tracks structure via diffraction pattern. Highlights: The method for determination of diffraction for 3D irregular object was developed. Developed method was applied for rotated conical surface. That method can be applied for rotated tracks in SSNTD. It was fond that diffraction pattern strongly depends track parameters. These results enable determination of inner tracks structure.